Personal profiles of fasting glucose as early indicators that antedate symptomatic diabetes mellitus - Hancheva, O. V.; Hrekova, Т. А.; Kadzharian, Ie. V.; Ганчева, Ольга Вікторівна; Грекова, Тетяна Анатоліївна; Каджарян, Єлизавета Віталіївна (Запорізький державний медичний університет, 2020)
Diabetes mellitus (DM) is a chronic and complex metabolic disease characterized by varying degree of hyperglycemia as a main laboratory characteristic. This condition must be detected early for timely and proper treatment as well as prevention of its microvascular and macrovascular complications.
Keywords: тези доповідей